A teoria social de Guerreiro Ramos: a formação de um habitus sociológico na periferia do capitalismo - Caldas, Alan (2021)
This thesis has as its object of study the social theory of the Brazilian sociologist Alberto Guerreiro Ramos (1915–1982), developed during the years 1935–1955. The main objective of this thesis is to analyse the author's journey through the Brazilian intellectual field and show how he formulated its social theory, both from the point of view of the social conditions and from of the structure of meaning that organizes its concepts. From a theoretical- methodological point of view, we use the concepts of habitus and social fields, derived from the work of French sociologist Pierre Bourdieu, with a hermeneutic perspective of interpretation of concepts. Our guiding hypothesis is that Ramos developed his sociological theory, especially between 1946 and 1953, conditioned, on the one hand, by the metatheory that the author adopted in his youth (between 1935–1943) and by his experience in institutions such as the Administrative Department of the Public Service, Black People's Experimental Theater (Teatro Experimental do Negro) and the Economic Advisory Office of the presidency of the second Vargas government. Of special note in this process was the author's confrontation with American sociology, especially that originating from the Chicago School, disseminated and consolidated in Brazil by Donald Pierson. For this intellectual combat the author used, in addition to the meta-theory of his youth, also the theories of blackness, ECLAC developmentalism and German sociology. We concluded that the author's social theory was structured as a sociology of knowledge capable of thinking about the imbalances of rationalization processes in the periphery of capitalism and also capable of providing subsidies for the individual to understand and overcome, within certain limits, their conditioning social.